IM means business. - Cherry, S.M (IEEE spectrum)
Instant messaging (IM), no longer just a facet of teenage life, now speeds everything from naval operations to customer service. IM is moving from computers and laptops to cellphones, PDAs, and other devices. Through its prosaic "buddy list," a continuously updated window that shows who among your family, friends, or colleagues are online and available, IM connects you to your inner circle in ways that phones and e-mail can't. What will make IM more than just the next hot idea to come and go is a single key feature called presence. In essence, this is a protocol to tell the world that you're available on a particular device. Outside IM, presence is being built into collaboration tools, word processors, e-mail directories, and even online games. Being always available has its drawbacks, of course. All too often, work and other obligations spill over into our private time. Many find the prospect of co-workers and even family always being able to contact us daunting. Concentration can be shattered; questions that seem important to the questioner may not be so to you. If usability researchers and application developers get it wrong, presence will be a burden, instead of a benefit. If they get it right, though, if they can deliver the right amount of your availability to the right set of people, IM can become the main way we initiate contact with the people we communicate with most often. indeed, those now-primary forms of communication, the telephone and e-mail, will either have presence built into them, or take a back seat to IM.